2006
DOI: 10.1021/om0601246
|View full text |Cite
|
Sign up to set email alerts
|

Palladium Pincer Complexes with Reduced Bond Angle Strain:  Efficient Catalysts for the Heck Reaction

Abstract: Palladium pincer complexes composed of six-membered fused metallacycles have been synthesized directly from 1,3-bis(2-pyridyloxy)benzene. The pincer complexes show remarkably high turnover numbers and frequencies in the Heck reaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(30 citation statements)
references
References 17 publications
1
29
0
Order By: Relevance
“…By now, palladacycles of different sizes have been reported, including six-membered cycles [2]. The most common six-membered palladacycles belong to the CN type and are derivatives of the following N-containing compounds: amidines (A) [3], 2-substituted pyridines (B [4][5][6][7][8][9][10][11][12], C [13,14] and D [15]), amines (E [16][17][18], F [16] and G [19]), azo compounds (H, X = N) [20], azines (I [21]), imines [H (X = CH) [22], I [23][24][25][26][27][28][29][30], J [31,32] and K [33][34][35]) and oxazolines (L [36], M [37], N [38] and O [39], Chart 1). CP [40] and CS [19,41] palladacycles of this size have also been obtained.…”
Section: Introductionmentioning
confidence: 99%
“…By now, palladacycles of different sizes have been reported, including six-membered cycles [2]. The most common six-membered palladacycles belong to the CN type and are derivatives of the following N-containing compounds: amidines (A) [3], 2-substituted pyridines (B [4][5][6][7][8][9][10][11][12], C [13,14] and D [15]), amines (E [16][17][18], F [16] and G [19]), azo compounds (H, X = N) [20], azines (I [21]), imines [H (X = CH) [22], I [23][24][25][26][27][28][29][30], J [31,32] and K [33][34][35]) and oxazolines (L [36], M [37], N [38] and O [39], Chart 1). CP [40] and CS [19,41] palladacycles of this size have also been obtained.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, this situation results in kinetically rather than thermodynamically controlled reaction pathways, and consequently, (ortho,para)-doubly metalated products rather than (ortho,ortho)-biscyclometallated species result [11]. Accordingly, we studied on the possibility of performing direct cyclometalation of NCN pincer ligands by screening appropriate metal sources and recently communicated our successful result in the synthesis of metal pincer complexes of achiral NCN ligands [12]. We also realized that chiral metal pincer complexes based on pyridine-based NCN ligands are rare, and thus initiated the synthesis of such metal pincer complexes for their potential applications to catalytic asymmetric reactions.…”
Section: Introductionmentioning
confidence: 99%
“…As a part of our continuing efforts on the synthesis, structural study and catalytic activity of pincer complexes [12], we report here the Pt(II)/Pd(II) complexes derived from the chiral pyridine based NCN pincer ligand. After completion of this work, we have found that the same but enantiomeric chloro-Pt(II)/Pd(II) complexes have been coincidentally pursued by other research group and their X-ray single crystal structures have been reported very recently [20].…”
Section: Introductionmentioning
confidence: 99%
“…16 The ligand 2-bromo-1,3-bis(indazol-2-ylmethyl)benzene (2), in its turn, was obtained by reaction of 2-bromo-1,3-bis(bromomethyl)benzene with 1H-indazole in refluxing toluene in the presence of Et 3 N. Interestingly, the reaction with 1H-indazole gives the isomer with the indazolyl groups bonded to the carbon spacer through the N2 atom because the electron pair located at this nitrogen becomes more reactive than the corresponding one to N1 (Scheme 1). Index ranges Moreover, an X-ray diffraction study was undertaken in order to obtain a complete characterization.…”
Section: Resultsmentioning
confidence: 99%
“…(3,5-dimethylpyrazol-1-ylmethyl)benzene (1) This compound was prepared by modification of a reported method. 16 In a Schlenk tube provided with a reflux condenser, 3,5-dimethylpyrazole (1.970 g, 20.5 mmol), KOH (2.314 g, 41.2 mmol), tetrabutylammonium bromide (TBAB, 0.212 g, 0.63 mmol) and water (1 mL) were stirred at room temperature for 25 min. 2-Bromo-1,3-bis(bromomethyl)benzene (3.291 g, 9.6 mmol) and toluene (25 mL) were then added and the mixture refluxed for 72 h. The resulting mixture was washed with water and the organic layer separated and dried with magnesium sulphate.…”
Section: General Remarksmentioning
confidence: 99%